2018
DOI: 10.1038/pr.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal developmental changes in the sensitivity of L-type Ca2+ channel to inhibition by verapamil in a mouse heart model

Abstract: BackgroundIn the clinical setting, verapamil is contraindicated in neonates and infants, because of the perceived risk of hypotension or bradyarrhythmia. However, it remains unclear whether there is an age-dependent difference in the sensitivity of cardiac L-type Ca channel current (I) to inhibition by verapamil.MethodsVentricular myocytes were enzymatically dissociated from the hearts of six different age groups (0, 7, 14, 21, 28 days, and 10-15 weeks) of mice, using a similar Langendorff-perfusion method. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…5 In addition, electrophysiological studies using a mouse heart have shown a higher sensitivity of ventricular L-type Ca 2þ channel current to verapamil in neonatal and infant stages than in child and adult stages. 7 These results suggest that myocardial responsiveness to calcium channel blockers changes with maturation and age. In addition, the evidence concerning fetal myocardial responses to calcium channel blockers in hypoxemic environment is limited.…”
Section: Introductionmentioning
confidence: 88%
“…5 In addition, electrophysiological studies using a mouse heart have shown a higher sensitivity of ventricular L-type Ca 2þ channel current to verapamil in neonatal and infant stages than in child and adult stages. 7 These results suggest that myocardial responsiveness to calcium channel blockers changes with maturation and age. In addition, the evidence concerning fetal myocardial responses to calcium channel blockers in hypoxemic environment is limited.…”
Section: Introductionmentioning
confidence: 88%
“…Patch pipettes (tip resistance was 2–3MΩ) were filled with the following solutions. The components of the pipette and bath solutions of the action potential, INa, Ito and ICa, L were described previously 6‐8 . All products were purchased from Sigma (Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Junction potential, capacitance and series resistance were automatically compensated in the whole‐cell configuration. The holding potential and the voltage clamp were operated as described 6‐8 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations